Teknik Komunikasi Persuasif Ustadzah Zainiyah Ma’ruf pada Upaya Meningkatkan Prestasi Belajar Siswa Kelas III Ma’hadul Qur’an Putri Pondok Pesantren Salafiyah Syafi’iyah Sukorejo Situbondo - Aminul ‘Alimin; Edy Supriyono (LP2M Universitas Ibrahimy, 2024)
Learning achievement is one of the proofs of student success in the learning process that takes place in an educational institution. However, in the process of achieving this learning achievement, students must process both internally and externally with various obstacles that accompany it. Teachers are one of the external factors that play a role in achieving student learning achievement. This study aims to determine the persuasive communication techniques applied by Ustadzah Zainiyah Ma'ruf on an effort to improve the learning achievement of Ma'hadul Qur'an students. This research is a type of qualitative research with a descriptive method. Data collection techniques with observation, interviews and ducumentation. To check the validity of the data, researchers use source triangulation. After this research process, the results of the research were obtained, that Ustadzah Zainiyah Ma'ruf as a teacher and homeroom teacher in improving the learning achievement of Ma'hadul Qur'an students, had used four persuasive communication techniques. The communication techniques in question include: association techniques, integration techniques, reward techniques, setting techniques, red herring. The five techniques can be applied well, but integration techniques produce significant changes. The integration technique referred to here, building communication between the dormitory leader, homeroom teacher and students, namely good communication becomes better. The dormitory president tries to establish more effective communication with homeroom teachers and students. This allows the growth of an increasing enthusiasm for learning based on good learning intentions and supported by a better learning process as well. One communication technique that is rarely used is the reward technique, why is that? Because the changes that occur there is an element of compulsion, there is a lure factor, not growing from one's own desires.